Synthesis and Multifunctionality of Self-Stabilized Poly(aminoanthraquinone) Nanofibrils - Li, X; Li, H; Huang, M; Moloney, M (2011)
Intrinsically self-stabilized nanofibril bundles of poly(1- aminoanthraquinone) (PAQ) were facilely synthesized by the chemical oxidative polymerization of 1-aminoanthraquinone. Critical polymerization parameters such as the monomer concentration, medium, oxidant species, temperature, and time were studied to significantly optimize the synthesis, size, properties, and multifunctionality of the resulting nanofibrils by IR, UV-vis, and fluorescence spectroscopy, X-ray diffraction, SEM, TEM, DSC, and thermogravimetry. It is found that the polymerization of 1-aminoanthraquinone with (NH4) 2S2O8 as an oxidant in HClO4/ acetonitrile without external stabilizer simply affords finer PAQ nanofibrils with an optimal combination of diameter of ca. 15 nm, a length of ∼6 μm, a higher preparation yield, a purer composition, a higher conductivity, and higher melting and decomposition temperatures than that with CrO3 and H2O2/Fe2+. Furthermore, the polymer nanofibrils exhibit high self-stability, powerful redispersibility, and a clean surface because of the complete avoidance of contamination from an external stabilizer. PAQ exhibits remarkably good solubility in polar solvents, colorful solvatochromism, widely controllable conductivity moving across 10 orders of magnitude from 10-9 to 50 S/cm, fluorescence, lead-ion adsorbability, high thermostability in air, and a very high carbon yield in nitrogen at 1000 °C. In particular, the nanoeffect of the PAQ nanofibrils with a large specific surface area and aspect ratio further enhances their fluorescence, lead-ion adsorbability, and nanocomposite ability of facilely forming a unique nanonetwork. PAQ would be useful as advanced materials including fluorescent emitters, sorbents of toxic metallic ions, cost-effective carbon foam precursors, and conducting nanocomposites with low percolation thresholds. © 2011 American Chemical Society.